Perencanaan Strategis Sistem Informasi Menggunakan Ward And Peppard Pada LPMP Provinsi Jambi - Prayitno, Budi; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2022)
The information system used to support the performance of a company / organization / agency has become something important. The information system that is utilized or developed should be able to provide added value or benefit to the company / organization / agency in achieving its objectives. In order for the information system currently in use to provide added value, it is necessary to have a good plan based on an analysis of the business environment and the information system environment being carried out. Currently, LPMP Provinsi Jambi does not yet have an information system strategic planning so that the development of information systems is still conditional. Therefore, a research was conducted to compile a strategic planning for information systems in LPMP Provinsi Jambi. This study uses the Ward and Peppard method with tools to analyze both the business environment and the information system environment. The tools used for this method are SWOT Analysis, PEST Analysis, Value Chain Analysis, Mc Farlan's Grid Portfolio. The final result of this research is a document of strategic planning information system of LPMP Provinsi Jambi. This document is expected to be part of the LPMP Provinsi Jambi strategic planning.